Analysis of Company Financial Performance Value Using the EVA (Economic Value Added) Method : A Study of State-Owned Bank Listed on the Indonesia Stock Exchange (IDX) 2020-2023 - Frans Charles Yuniarto; Rizki Aprilia Dwi Susanti; Moh. Askiyanto (International Journal of Management and Business, 2026)
The aim of this research is to determine the financial performance of state-owned banks, namely Bank Mandiri, BRI, and BNI, in terms of Economic Value Added (EVA) analysis. This study employs a qualitative research method. The instruments for this research include financial reports from the state-owned banks Bank Mandiri, BRI, and BNI for the years 2020-2023. Data analysis uses Net Operating Profit After Tax (NOPAT), Invested Capital, Weighted Average Cost Of Capital (WACC), Capital Charges, and Economic Value Added (EVA) calculations. Overall, all three banks, Bank Mandiri, BRI, and BNI, consistently generated positive Economic Value Added (EVA > 0) during the period of 2020-2023, with an average overall EVA of Rp. 27,953,407 (in millions). This positive EVA value indicates that the three banks have successfully created economic value added for shareholders, where the net operating profit after tax (NOPAT) generated exceeds the capital charges incurred.